Enhancing Information Literacy through Generative AI in the Library Classroom - Denise A. Wetzel; Justin Kani (Pennsylvania Libraries: Research & Practice, 2025)
This article explores the integration of a generative AI chatbot into undergraduate education to enhance information literacy. By leveraging the ACRL Framework for Information Literacy, specifically the 'Scholarship as Conversation', 'Research as Inquiry', and 'Searching as Strategic Exploration' frames, the authors argue that AI tools can improve students' research skills while emphasizing the importance of critical reading and resource verification. Using scaffolding with AI supports students transitioning from their current skill levels to achieving specific learning objectives. The paper reviews the impact of generative AI on higher education and proposes two adaptable assignments for classroom use. The article concludes that effective use of AI in educational settings can enhance learning outcomes and prepare students for the complexities of modern research practices while promoting ethical information usage.